Urinary trypsinogen-2 dipstick test for point-of-care screening of acute pancreatitis - Raja, Bhuvaneswari; T. S., Srinath Kumar; V., Viju Wilben (International Journal of Research in Medical Sciences, 2019)
Background: Acute pancreatitis (AP) is associated with high mortality in its severe form. Conventional laboratory tests used in its diagnosis are fraught with multiple shortcomings. Early institution of intravenous fluid resuscitation can reduce morbidity and mortality. Measurement of urinary trypsinogen-2 using a bedside urine dipstick test may prove useful in early identification of AP. Methods: Patients with symptoms consistent with AP, attending the emergency department, at a tertiary care hospital in southern India, between November 2014 and November 2016, were included in a prospective observational study. The patients underwent routine investigations and additionally were tested with a urinary trypsinogen-2 dipstick test (UTT). The diagnostic performance and the time to reporting of the different investigations were compared with those of UTT. Final diagnosis of AP, made by clinicians, served as the standard. Results: The sensitivities of serum amylase, serum lipase, UTT, ultrasonography (USG) and contrast-enhanced computed tomography (CECT) were 97.1%, 94.1%, 92.7%, 98.3% and 100%, respectively. The respective specificities were 92.4%, 98.5%, 98.5%, 100% and 100%. The average time required to obtain the test report was about half hour from admission in case of UTT, compared to about 3 hours for serum amylase/lipase, 4 hours for USG and 6 hours for CECT. Conclusions: The results indicate that UTT test, due to its high performance indices, simplicity and faster availability of reports, can serve as an ideal screening test for AP and help in early institution of treatment.